Sleep is enhanced in aged male mice that overexpress calcium/calmodulin-dependent protein kinase IV - Feeney, Sierra P.; Threlfall, Erin; Bilboa, James M.; Angelakos, Christopher C.; Wimmer, Mathieu E.; Kida, Satoshi; Abel, Ted; Tudor, Jennifer C. (Frontiers in Neuroscience, 2025)
The dysregulation of sleep–wake patterns that occurs during aging is well documented and coincides with changes in intracellular signaling pathways that regulate sleep, such as the calcium/calmodulin-dependent protein kinase (CaMKII)/cyclic-AMP response element-binding protein (CREB) pathway. However, much less is known about the relationship between other CREB-activating members of the CaMK family, such as calcium/calmodulin-dependent protein kinase IV (CaMKIV), and the regulation of sleep. Using 2- to 4-month-old (young adult) and 22- to 24-month-old (aged) male and female CaMKIV-overexpressing (CaMKIV-OE) mice, we observed that overexpression of CaMKIV in the forebrain decreased wakefulness and increased the amount of non-rapid eye movement (NREM) and rapid eye movement (REM) sleep in aged male mice, but not young adult male mice, in comparison to age- and sex-matched controls. Conversely, female mice overexpressing CaMKIV displayed no significant differences in the percentage of time spent in each vigilance state compared to their wild-type counterparts, regardless of age. While CaMKIV overexpression also led to more sleep–wake fragmentation in young adult and aged male mice, aged female mice displayed more consolidated NREM sleep. Overall, our results suggest that CaMKIV overexpression enhances sleep in aged male mice, and differentially affects sleep–wake architecture based on sex and age, providing insights into the potential mechanism by which CaMKIV overexpression enhances memory.